Developing a case based learning curriculum with a salutogenic perspective. (September 2018) - Ridley, Neesha; Byrom, Anna
Abstract: At the University of Central Lancashire, in the North West of England, United Kingdom (UK) the midwifery team introduced a new and innovative case-based learning (CBL) curriculum for the undergraduate midwifery course. CBL is a student-centred approach to teaching and learning and encourages students to learn from each other, develop essential skills when caring for women and families including collaborative working and effective communication. In this article we share our approach and experiences of developing and delivering a CBL curriculum informed by salutogenesis, including how it enabled us to support effective learning and skill development for women and families.